Factors associated with anaemia among pregnant women in Rwanda: an analysis of the Rwanda demographic and health survey of 2020 - Lilian Nuwabaine; Joseph Kawuki; Livingstone Kamoga; Quraish Sserwanja; Ghislaine Gatasi; Elorm Donkor; Linet M Mutisya; John Baptist Asiimwe (BMC, 2024)
Abstract Background Anaemia in pregnancy is associated with several adverse outcomes for mothers and newborns, as well as their families. In this study, we assessed the prevalence of anaemia and the associated factors among pregnant women in Rwanda. Methods Secondary data from the 2020 Rwanda Demographic and Health Survey (RDHS) was used. Multistage stratified sampling was used to select 435 pregnant women included in the study. Anaemia among pregnant women was defined as a haemoglobin value < 11 g/dL. Multivariable logistic regression was used to assess the associated factors with anaemia in pregnancy, using SPSS (version 26). Results Of the 435 pregnant women, 24.6% (95%CI: 21.1-29.3) were anaemic (1 in 4 pregnant women). Not working (AOR = 2.45; 95%CI: 1.14-5.26), being unmarried (AOR = 1.23; 95%CI: 1.24-3.57), low wealth index (AOR = 9.19; 95%CI: 1.64-51.56), having difficulty accessing a nearby health facility (AOR = 5.40; 95%CI: 2.21-13.23), and normal body mass index (AOR = 3.33; 95%CI: 1.46-7.59) were associated with higher odds of being anaemic. However, not taking iron supplements (AOR = 0.16; 95% CI: 0.04-0.67), having no exposure to television (AOR = 0.35; 95%CI: 0.14-0.91), being from the southern region (AOR = 0.14; 95% CI: 0.03-0.66), and low husband/partner's education (AOR = 0.08; 95% CI: 0.01-0.59) were associated with lower odds of being anaemic. Conclusions The study findings indicate a high prevalence of anaemia in pregnancy, which was associated with several socio-demographics. There is a need for setting up mobile clinics and health facilities in hard-to-reach areas for easy accessibility to early anaemia screening services. Conducting mass screening for anaemia targeting pregnant women who are not working, the unmarried, and those with a low wealth index would also be beneficial. The intake of locally available iron rich foods and/ or bio-fortified foods is also recommended.